Survey of types and use of traditional medicinal plants for beef cattle in Bontang City - Amar Ma'ruf Fachrul Mu'minin; Lilik Maslachah; Sri Hidanah; Ratna Damayanti; Kadek Rachmawati; Mohammad Sukmanadi (Universitas Airlangga, 2024)
Bontang city is suitable for research due to the limited data on the use of traditional herbal medicine in beef cattle. This study aims to survey the types and usage of traditional herbal plants in beef cattle in Bontang city, providing new insights for local farmers. Data collection involved observation, recording, and photographic documentation. Samples were taken from Bontang city, including West Bontang, South Bontang, and North Bontang districts. Traditional medicinal plants such as garlic, brotowali, coconut, turmeric, temulawak, guava, and lime thrive in these conditions. The majority of respondents are beef cattle farmers aged 51-60 years with a low level of education. Experience in cattle farming for more than 4 years has improved their skills and productivity. The primary source of information on herbal plants is passed down through generations from their parents. The results of the survey on the types and usage of traditional herbal plants in beef cattle in Bontang city can be summarized as follows. Seven plant species are used by beef cattle farmers as natural remedies, namely garlic, brotowali, coconut, turmeric, temulawak, guava, and lime.